Short-term prognosis, mid- and long-term clinical follow-up of bronchoscopic intervention therapy combined with bronchial artery embolization on massive hemoptysis - Li, Kunying; Lian, Taomei; Wang, Zhenjing; Zhang, Zhengxun; Wang, Wenbo; Qian, Jiaping (Frontiers in Surgery, 2025)
BackgroundTo explore the short-term prognosis, mid- and long-term clinical follow-up of bronchoscopic intervention therapy (BIT) combined with bronchial artery embolization (BAE) in the treatment of massive hemoptysis.MethodsPatients with massive hemoptysis who received BAE (BAE group) or BAE combined with BIT (BAE & BIT group) based on standard clinical treatment were included retrospectively, during June 2022 and March 2023. The short-term prognosis assessed by the therapeutic response, hemoptysis recurrence rates at 1-month post-surgery, and postoperative complications were compared. Mid- and long-term clinical follow-up data were collected.ResultsData were collected from 136 patients. There were 68 patients (aged 21–60 years, 31 males) received BAE & BIT, and 68 patients (aged 20–59 years, 36 males) received BAE were matched. After surgery, the immediate response rate and total response rate in BIT & BAE group were significantly higher than those in BAE group, while comparable hemoptysis recurrence rates at 1-month post-surgery. Patients in BIT & BAE group had significantly lower rates of postoperative complications, including obstructive pneumonia lung consolidation, and atelectasis, compared to those in BAEgroup. No death in the BIT & BAE group, while the BAE group experienced 3 intraoperative deaths and 4 cases requiring conversion to surgical intervention. No recurrence was observed during the mid-term and long-term follow-up.ConclusionCompared to BAE alone, BIT combined with BAT may offer better short-term prognosis, including higher response rate, lower rates of postoperative complications and mortality, in the management of massive hemoptysis, with a good mid- and long-term therapeutic effects.